Glucosamine-loaded injectable hydrogel promotes autophagy and inhibits apoptosis after cartilage injury - Yijin Chang; Yaguang Wang; Jiansheng Liu; Xu Chen; Xuejing Ma; Yu Hu; He Tian; Xiaomei Wang; Changzheng Mu (Heliyon, 2023)
The ability of cartilage to regenerate and repair is limited. N-acetyl- d-glucosamine (GlcNAc) is a nutritional supplement commonly used to activate chondrocytes. To prolong the duration of action of GlcNAc and improve its curative effect after cartilage injury, a GlcNAc thermosensitive hydrogel is prepared based on Pluronic F127 (PF127). The physicochemical properties results indicate that this hydrogel is injectable and retards the release of GlcNAc. Further, the therapeutic benefits of GlcNAc hydrogel are detected through intra-articular injection in rat specimens with cartilage injury. Behavioral experiments results indicate that the rats treated with GlcNAc hydrogel had longer step lengths, smaller foot angles and slower fall times. Compared with the sham group, the expression of Sox9 was 1.5 times and the level of collagen II was 2.4 times in the hydrogel treated group. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining result confirmed that the GlcNAc hydrogel reduce apoptosis by about 50%. Our results of immunohistochemical staining, Western blotting assays and enzyme activity detection all suggested that GlcNAc hydrogel reduce the expression of cleaved-caspase3 and caspase8 (Compared to the sham group, the protein contents were reduced by about 50% in the GlcNAc hydrogel group). We also found that GlcNAc hydrogel activates autophagy through ERK signal pathway. The results of Western blotting indicated that GlcNAc hydrogel increase the levels of LC3B and Becline1 (hydrogel group & sham group, LC3B: 1.56 ± 0.07 & 1.00 ± 0.14; Becline1: 1.98 ± 0.07 & 1.00 ± 0.13). Whereas, the content of P62 reduced after GlcNAc hydrogel treatment, the relative level in sham group and hydrogel group are 1.00 ± 0.02 and 0.73 ± 0.06. Our results revealed that the number of P-ERK positive cells in the hydrogel group (57.36 ± 3.56%) was higher when compared with the sham (24.82 ± 2.72%). And, the ratio of P-ERK and ERK was higher than that in the sham group (1.48 ± 0.07 & 1.00 ± 0.08). The GlcNAc thermosensitive hydrogel is a promising and sustainable drug delivery system for intra-articular injection in the treatment of cartilage injury.